Tipologi Visual Batik Betawi : Analisis Negosiasi Artistik Sanggar Batik Betawi Terogong dan Gandaria Jakarta - Damar rangga putra; Ida Ayu Trisnawati; I Ketut Sida Arsa; Ida Ayu Kade Sri Sukmadewi (Kartala Virtual Studies, 2026)
This research aims to analyze the transformation of Batik Betawi visual motifs as a response to Jakarta provincial government policies and urban market dynamics. Utilizing Pierre Bourdieu's social practice theory, this study examines how artisans at Sanggar Terogong and Gandaria navigate artistic negotiations between official government iconography and local collective memory. The research employs a qualitative method through field observations and in-depth interviews. The findings reveal a visual polarization: on one hand, artisans produce popular iconic motifs such as Monas and Ondel-ondel to meet policy legitimacy standards (symbolic capital); on the other hand, they conserve agrarian memories through endemic floral motifs like Mengkudu and Salak Condet as a form of symbolic resistance. The study concludes that the contemporary visual identity of Batik Betawi is the result of a dialectic between top-down policy interventions and bottom-up artisan habitus.